On the prospects of using metal hydrides in nuclear energy - M. I. Vlasenko; M. M. Korotenko; S. L. Lytvynenko; D. V. Pyshna; I. A. Morozov; D. P. Stratilat; I. A. Khomych; O. P. Budnyk4 (Ядерна фізика та енергетика)
he results of analytical and experimental studies of neutron-protective properties of a number of domestic materials and of the SWX-277 material (manufactured in the USA) are reported. SWX-277 is employed for protection against neutron irradiation in containers for dry storage of spent nuclear fuel in the Zaporizhzhya Nuclear Power Plant (NPP). The results of studies have confirmed the high protective properties of some domestic materials (in particular, titanium hydride), and the perspective of their wider use for protection against neutron irradiation.